Conceptions of place in Old English poetry - Brockbank, W (2022)
Previous studies of place and space in Anglo-Saxon literature and culture have tended to focus on the engagement with these phenomena as a means of understanding the world and of imposing order on it. The analysis offered here scrutinises instead the literary representation and function of place in the vernacular poetic tradition, as well as its symbolic significance. In its examination of conceptions of place in Old English poetry, this thesis contends that place is fundamentally fleeting and symbolic of the transience of all earthly things.